Estado da arte da cromatografia gasosa de alta resolução e alta temperatura State of the art of high temperature high resolution gas chromatography - Alberto dos Santos Pereira; Francisco Radler de Aquino Neto (Química Nova, 2000)
The developments in stationary phase synthesis and capillary column technology, have opened new perspectives in analysis of high molecular mass compounds (³600 daltons) and thermolabile organic compounds by High Temperature High Resolution Gas Chromatography (HT-HRGC). HT-HRGC is a new analytical borderline and its application to the analysis of high molecular mass compounds is still in its infancy. The apolar and medium polar gum phases can now be operated at temperatures up to 400-480ºC, being used for the analysis of n-alcanes up to C-100, lipids, oligosaccharides, industrial resins, polyglycerols, cyclodextrins, porphyrins, etc. This technique should play a leading role as a powerful tool, for many different analysis types, in multidisciplinary fields of Science.